Clinical and economic impact of intensive care unit-acquired bloodstream infections in Taiwan: a nationwide population-based retrospective cohort study - Shu-Chen Kuo; Yung-Chih Wang; Shu-Man Shih; Yung-Tai Chen; Chao Agnes Hsiung (BMJ Open)
Objectives To estimate the clinical and economic impact of intensive care unit-acquired bloodstream infections in Taiwan.Design Retrospective cohort study.Setting Nationwide Taiwanese population in the National Health Insurance Research Database and the Taiwan Nosocomial Infections Surveillance (2007–2015) dataset.Participants The first episodes of intensive care unit-acquired bloodstream infections in patients ≥20 years of age in the datasets. Propensity score-matching (1:2) of demographic data, comorbidities and disease severity was performed to select a comparison cohort from a pool of intensive care unit patients without intensive care unit-acquired infections from the same datasets.Primary and secondary outcome measures The mortality rate, length of hospitalisation and healthcare cost.Results After matching, the in-hospital mortality of 14 234 patients with intensive care unit-acquired bloodstream infections was 44.23%, compared with 33.48% for 28 468 intensive care unit patients without infections. The 14-day mortality rate was also higher in the bloodstream infections cohort (4323, 30.37% vs 6766 deaths, 23.77%, respectively; p<0.001). Furthermore, the patients with intensive care unit-acquired bloodstream infections had a prolonged length of hospitalisation after their index date (18 days (IQR 7–39) vs 10 days (IQR 4–21), respectively; p<0.001) and a higher healthcare cost (US$16 038 (IQR 9667–25 946) vs US$10 372 (IQR 6289–16 932), respectively; p<0.001). The excessive hospital stay and healthcare cost per case were 12.69 days and US$7669, respectively. Similar results were observed in subgroup analyses of various WHO’s priority pathogens and Candida spp.Conclusions Intensive care unit-acquired bloodstream infections in critically ill patients were associated with increased mortality, longer hospital stays and higher healthcare costs.